MATHEMATICS FOR MARINE ENGINEERS - Corner, Kevin; Jackson, Leslie; Embleton, William (Reeds marine engineering and technology, 2018)
This exciting new edition covers the core subject areas of arithmetic, algebra, mensuration in 2D and 3D, trigonometry and geometry, graphs, calculus and statistics and probability for Marine Engineering students for the Merchant Navy OOW qualification. Initial examples have been designed purely to practise mathematical technique and, once these skills have been mastered, further examples focus on engineering situations where the appropriate skills may be utilised. The practical questions are primarily from a marine engineering background but questions from other disciplines, such as electrical engineering, will also be covered, and reference made to the use of advanced calculators where relevant